Complications of Percutaneous Biliary Procedures - Molina, Heather; Chan, Maye M.; Lewandowski, Robert J.; Gabr, Ahmed; Riaz, Ahsun (Seminars in Interventional Radiology, 2021)
Percutaneous biliary and gallbladder drainage is routinely performed by interventional radiology. These pathologies and techniques are well described in the literature and in this issue. The purpose of this review is to focus on the recognition and management of complications. Percutaneous biliary drains can have a variety of complications which can range from minor skin issues to more serious and complex bleeding issues. Advancements in imaging and techniques improve the safety profile of percutaneous biliary and gallbladder interventions.
Keywords: biliary interventions; percutaneous transhepatic cholangiography; biliary drains